Advances in the study of behavior. (Advances in the study of behavior, 1992)
Advances in the Study of Behavior remains one of the most-turned-to sources for penetrating insight on the latest findings in behavior research. This serial has kept pace with the vigorous multidisciplinary growth of the field and covers all major aspects, from ecology to endocrinology, in both human and animal subjects. Critical reviews, presentations of major research programs, and communication of significant new concepts provide readers with an up-to-date overview of the latest developments in this field. The series does not focus narrowly on one or a few fields, but features articles covering the best behavioral work from a wide spectrum. The skill and concepts of scientists in such diverse fields necessarily differ, making the task of developing cooperation and communication among them a difficult one. But it is one that is of great importance, and one to which the editors and publisher of Advances in the Study of Behavior are committed. Each volume of Advances in the Study of Behavior contains an index, and each chapter includes references.